2007
DOI: 10.1007/s12094-007-0030-7
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolic disease in cancer. Optimisation of the use of antithrombotic agents

Abstract: Venous thromoboembolism is one of the most common complications in cancer patients and may have serious consequences. At present, most clinical oncologists report using thromboprophylaxis in less than 5% of patients. One of the possible reasons for this limited use is the lack of oncology specific guidelines. In effect, while there are excellent guidelines for optimising the use of antithrombotic agents to prevent and treat thromboembolism, they must be adapted to the concrete context of cancer patients. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 121 publications
0
1
0
Order By: Relevance
“…In the present study, we investigated risk factors related to postoperative VTE in patients with gynecologic disease who received both IPC and anticoagulant therapy. Among cancer patients, Camps et al reported that ovarian cancer follows pancreatic, gastric, urological, and brain cancer as the disease with the highest risk of VTE [9]. Since it is therefore quite possible that VTE will have already occurred before the start of treatment, it is important to undertake preoperative screening of ovarian cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we investigated risk factors related to postoperative VTE in patients with gynecologic disease who received both IPC and anticoagulant therapy. Among cancer patients, Camps et al reported that ovarian cancer follows pancreatic, gastric, urological, and brain cancer as the disease with the highest risk of VTE [9]. Since it is therefore quite possible that VTE will have already occurred before the start of treatment, it is important to undertake preoperative screening of ovarian cancer patients.…”
Section: Introductionmentioning
confidence: 99%